High-performance wear-resistant composite lining plate and preparation method thereof
By adopting a composite structure of ceramic layer, rubber layer and steel plate layer, the wear and corrosion problems of existing lining plates in high hardness, high flow rate material erosion and corrosive media are solved, and the preparation of high-performance wear-resistant composite lining plates is realized, extending service life and improving economic benefits.
Patent Information
- Application Number
- CN202510177616.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-18
- Publication Date
- 2025-04-22
AI Technical Summary
The existing lining plates wear quickly when facing high hardness and high flow velocity materials, and are easily corroded and damaged in corrosive media, resulting in material leakage and safety accidents.
The composite structure of a ceramic layer, a rubber layer and a steel plate layer is adopted. The ceramic layer is prepared from high-purity alumina powder and titanium dioxide. The rubber layer is prepared by ultrasonic dispersing carbon nanotubes and cross-linking reaction. The steel plate layer is heat-dipped zinc-dipped. These layers are assembled by hot pressing to form a composite lining that is resistant to wear and corrosion.
It improves the wear resistance, corrosion resistance and flush resistance of the lining plate, extends the service life, reduces the number of maintenance times, and improves production efficiency and economic benefits.
Smart Images

Figure BDA0005276024020000151
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to a high-performance wear-resistant composite lining plate and a preparation method thereof. Background Art
[0002] In the industrial field, linings are used in mining, power, metallurgy, chemical and other industries. However, ordinary linings wear very quickly when faced with materials with high hardness and high flow rate. For example, in mining, the excavation and transportation of ore frequently contact with the conveying pipeline and silo lining, resulting in a short service life of the lining and frequent replacement, which seriously affects production efficiency and increases production costs. In the chemical industry, many materials are highly corrosive, such as acid and alkali solutions. Under the long-term action of such corrosive media, ordinary linings are easily corroded and damaged, resulting in material leakage, which not only causes material waste, but also may cause safety accidents and environmental pollution problems. In some occasions involving the transportation of large-particle materials, such as the coal transportation system of thermal power plants, the large-particle coal has a strong scouring effect on the lining during high-speed transportation. Ordinary linings are difficult to withstand this impact and are prone to breakage and falling off, affecting the normal operation of the equipment. Summary of the invention
[0003] The purpose of the present invention is to provide a high-performance wear-resistant composite lining and a preparation method thereof. The prepared composite lining has excellent wear resistance, strong corrosion resistance, and good erosion resistance, and can reduce the number of maintenance times, thereby improving the economic benefits of the enterprise.
[0004] To achieve the above-mentioned purpose, the present invention provides a high-performance wear-resistant composite lining plate, comprising a ceramic layer, a rubber layer and a steel plate layer, wherein a rubber layer is sandwiched between the steel plate layer and the ceramic layer.
[0005] The above-mentioned method for preparing a high-performance wear-resistant composite lining plate comprises the following steps:
[0006] Step 1: preparing a ceramic layer;
[0007] Step 2, preparing a rubber layer;
[0008] Step 3: Pretreatment of steel plate layer;
[0009] Step 4: Assemble the ceramic layer, rubber layer and steel plate layer, and perform post-processing.
[0010] Preferably, the specific operation of step one is: adding the raw materials into a planetary ball mill and ball milling with anhydrous ethanol as the medium, fully mixing the raw materials to obtain a slurry, pouring the slurry into a mold, placing the mold in a static press to form a ceramic body, placing the ceramic body in a high-temperature electric furnace to heat it, and then cooling it to room temperature with the furnace to obtain a ceramic layer.
[0011] Preferably, the specific operation of step two is: dissolving the shape memory rubber in an organic solvent, adding the smart hydrogel precursor and carbon nanotubes, and uniformly dispersing the carbon nanotubes in the solution through ultrasonic dispersion and mechanical stirring, then pouring the mixed solution into a mold and adding an initiator for a cross-linking reaction, obtaining a smart responsive multifunctional rubber layer after the reaction, and removing the smart responsive multifunctional rubber layer from the mold after cooling to room temperature.
[0012] Preferably, the specific operation of step three is: cleaning the surface of the steel plate, applying a layer of special primer on the cleaned surface of the steel plate and drying it to obtain a steel plate layer.
[0013] Preferably, the specific operation of step four is: cutting the intelligent response multifunctional rubber layer into a suitable size, placing it between the ceramic layer and the steel plate layer, placing the stacked components into a vulcanizer for hot pressing to composite the ceramic layer, the rubber layer and the steel plate layer into one, and polishing the obtained material to finally obtain a composite lining.
[0014] Preferably, the raw materials in step one are high-purity alumina powder and 3-5% titanium dioxide, the material-ball ratio in the ball mill is 1:3-5, the ball milling time is 8-12h, the rotation speed is 300-500r / min, the pressure in the static press is 150-200MPa, the pressure is maintained for 5-10min, the heating temperature in the high-temperature electric furnace is 1650-1700℃, the heating time is 3-5h, and the heating rate is 5-10℃ / min.
[0015] Preferably, in step 2, the shape memory rubber comprises one of thermoplastic polyurethane and silicone rubber-based shape memory rubber, the organic solvent comprises one of DMF and THF, and the smart hydrogel precursor comprises one or more of N-vinyl caprolactam, acrylic acid, N,N'-methylenebisacrylamide and ammonium persulfate;
[0016] The mass ratio of shape memory rubber to organic solvent is 1:8-12, the mass ratio of smart hydrogel precursor to shape memory rubber is 1:2-10, the oil bath reaction temperature is 50-100°C, the reaction time is 4-6h, the mass ratio of carbon nanotubes to shape memory rubber is 0.01-0.1:1, the ultrasonic power is 100-500W, the ultrasonic time is 1-2h, the stirring speed is 300-500r / min, and the stirring time is 2-3h;
[0017] The initiator accounts for 1-5% of the total mass of the smart hydrogel precursor, the temperature of the cross-linking reaction is 50-100° C., and the reaction time is 6-8 hours.
[0018] Preferably, the primer in step three is an epoxy primer, and the drying time is 1-2 hours.
[0019] Preferably, in step 4, the hot pressing molding temperature is 140-150° C., the pressure is 10-15 MPa, and the hot pressing time is 15-25 min.
[0020] Therefore, the present invention adopts the above-mentioned high-performance wear-resistant composite lining plate and its preparation method, which has the following beneficial effects:
[0021] (1) The ceramic layer made of high-purity alumina powder and titanium dioxide, combined with the cushioning of the rubber layer, greatly improves the wear resistance, extends the service life of the liner, reduces the number of replacements, and improves production efficiency.
[0022] (2) The ceramic layer, rubber layer and treated steel plate layer form a multi-layer protection, which can effectively resist chemical corrosion such as acid and alkali, avoid lining damage due to corrosion, and reduce maintenance costs.
[0023] (3) The hardness of the ceramic layer and the elasticity of the rubber layer work together to enable the liner to withstand the erosion of large particles and maintain structural integrity.
[0024] The technical solution of the present invention is further described in detail below through embodiments. DETAILED DESCRIPTION
[0025] The technical solution of the present invention is further illustrated by the following examples.
[0026] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.
[0027] The invention provides a high-performance wear-resistant composite lining plate, comprising a ceramic layer, a rubber layer and a steel plate layer, wherein a rubber layer is sandwiched between the steel plate layer and the ceramic layer.
[0028] The above-mentioned method for preparing a high-performance wear-resistant composite lining plate comprises the following steps:
[0029] Step 1: Prepare a ceramic layer: Add raw materials into a planetary ball mill and perform ball milling with anhydrous ethanol as the medium. The raw materials are fully mixed to obtain a slurry, which is poured into a mold. The mold is placed in a static press to form a ceramic body, which is placed in a high-temperature electric furnace to heat, and then cooled to room temperature to obtain a ceramic layer.
[0030] The raw material is high-purity alumina powder with a purity of more than 95%. 3-5% titanium dioxide is added. The addition of titanium dioxide can effectively improve the crystal structure of the ceramic layer and enhance its wear resistance and corrosion resistance. The material-ball ratio in the ball mill is 1:3-5, the ball milling time is 8-12h, and the rotation speed is 300-500r / min. By precisely controlling the ball milling parameters, the raw materials are fully mixed, laying the foundation for the subsequent formation of a uniform and dense ceramic structure. The pressure in the static press is 150-200MPa, the pressure is maintained for 5-10min, the heating temperature in the high-temperature electric furnace is 1650-1700℃, the heating time is 3-5h, and the heating rate is 5-10℃ / min. High-temperature sintering densifies the ceramic body and improves the hardness and wear resistance of the ceramic layer. The ceramic layer is placed in a 10% hydrochloric acid solution and soaked at 50-100℃ for 12-24h. After inspection, the mass loss is only 0.5%, showing good corrosion resistance.
[0031] High-purity alumina powder (more than 95%) has high hardness, high strength and good chemical stability, and is the basic material for the wear-resistant and corrosion-resistant ceramic layer. Adding 3-5% titanium dioxide can induce solid solution strengthening and other effects. During the high-temperature sintering process of titanium dioxide, titanium ions (Ti 4+ ) can partially replace the aluminum ions (Al 3+ ), which distorts the crystal lattice, thereby hindering dislocation movement and enhancing the hardness and wear resistance of ceramic materials. At the same time, this lattice distortion may also affect the electron cloud distribution on the ceramic surface, change its chemical reaction activity with corrosive media such as acids and alkalis, and improve corrosion resistance.
[0032] Step 2, prepare the rubber layer: dissolve the shape memory rubber in an organic solvent for oil bath reaction, add the smart hydrogel precursor and carbon nanotubes, and evenly disperse the carbon nanotubes in the solution through ultrasonic dispersion and mechanical stirring. Then pour the mixed solution into the mold and add the initiator for cross-linking reaction. After the reaction, the smart response multifunctional rubber layer is obtained. After soaking in a solution simulating acid-containing materials for 3 months, the hardness of the rubber layer changes within the range of ±5, and the tensile strength retention rate is 85%, indicating that it has good corrosion resistance and stability in this acidic environment. Then take out the mold, and take out the smart response multifunctional rubber layer from the mold after cooling to room temperature. After cooling to room temperature, take out the smart response multifunctional rubber layer from the mold.
[0033] In step 2, the shape memory rubber includes one of thermoplastic polyurethane and silicone rubber-based shape memory rubber, the organic solvent includes one of DMF and THF, and the smart hydrogel precursor includes one or more of N-vinyl caprolactam, acrylic acid, N,N'-methylenebisacrylamide and ammonium persulfate, wherein N-isopropylacrylamide (NIPAAm) is used as a temperature-sensitive monomer, acrylic acid (AAc) is used as a moisture-sensitive monomer, N,N'-methylenebisacrylamide (MBA) is used as a cross-linking agent, and ammonium persulfate (APS) is used as an initiator, wherein the molar ratio of N-vinyl caprolactam, acrylic acid, N,N'-methylenebisacrylamide and ammonium persulfate is: NIPAAm:AAc:MBA:APS=8:2:0.1:0.01.
[0034] The mass ratio of shape memory rubber to organic solvent is 1:8-12, the mass ratio of smart hydrogel precursor to shape memory rubber is 1:2-10, the oil bath reaction temperature is 50-100°C, the reaction time is 4-6h, the mass ratio of carbon nanotubes to shape memory rubber is 0.01-0.1:1, the ultrasonic power is 100-500W, the ultrasonic time is 1-2h, the stirring speed is 300-500r / min, and the stirring time is 2-3h;
[0035] The initiator accounts for 1-5% of the total mass of the smart hydrogel precursor, the temperature of the cross-linking reaction is 50-100° C., and the reaction time is 6-8 hours.
[0036] Shape memory rubber (thermoplastic polyurethane or silicone rubber-based shape memory rubber) has a unique molecular structure, which enables it to return to its original shape under certain conditions, while having good flexibility and elasticity. DMF or THF is selected as an organic solvent because they have good compatibility with shape memory rubber. Under oil bath conditions, the rubber can be fully dissolved to form a uniform solution system, providing a basis for the uniform dispersion of subsequent additives.
[0037] The smart hydrogel precursor can undergo a polymerization reaction to form a hydrogel structure. The hydrogel is environmentally responsive and can sense changes in external temperature, humidity, etc. It can adapt to the environment by swelling or shrinking itself, giving the rubber layer smart response characteristics.
[0038] In order to verify whether the intelligent response multifunctional rubber layer has intelligent response characteristics, the following operations were performed:
[0039] (1) Temperature response experiment:
[0040] Use a high-precision thermostat to control the temperature within the range of 20-60°C, with a temperature fluctuation of no more than ±0.5°C. Suspend the sample in the thermostat and equip it with a high-precision displacement sensor to measure the dimensional changes of the sample at different temperatures.
[0041] First, the prepared intelligent response multifunctional rubber layer sample was placed in a constant temperature box with an initial temperature of 20°C. After stabilization for 30 minutes, the reading of the displacement sensor was recorded as the initial length L0. The temperature was gradually increased at intervals of 5°C. After each temperature increase, 30 minutes were waited to allow the sample to reach thermal equilibrium. The reading of the displacement sensor at this time was recorded as L0. i , and calculate the length change rate of the sample at different temperatures:
[0042] ΔL=(L i -L0) / L0
[0043] Continue to heat up to 60°C to complete the measurement of the heating process. Then gradually cool down at the same temperature interval, repeat the above measurement steps, and record the length change rate of the sample during the cooling process.
[0044] Table 1 Length change rate
[0045] Temperature(℃) Length change rate (%) 20 0 25 2.3 30 4.8 35 7.6 40 11.5 45 15.5 50 19.5 55 23.5 60 27.5
[0046] It can be seen from the data that the length change rate of the sample increases under the same temperature change, indicating that the temperature sensitivity is enhanced.
[0047] (2) Humidity response experiment
[0048] Construct a closed environment with controlled humidity, use a high-precision humidity generator and humidity sensor, and accurately control the ambient humidity within the range of 20%-90% relative humidity (RH), with humidity fluctuations not exceeding ±2%. Place the sample in the humidity environment, and measure the mass change of the sample at different humidity levels by weighing.
[0049] Place the sample in a dry environment (humidity of 20% RH) for 24 hours to reach constant weight, record the mass m0 at this time, gradually increase the ambient humidity, each increase of 10% RH, maintain for 24 hours, allow the sample to fully absorb or release water, reach equilibrium, record the mass m at this time i , calculate the mass change rate of the sample at different humidity:
[0050] Δm=(m i -m0) / m0;
[0051] Continue to increase the humidity to 90% RH, complete the measurement of the humidity increase process, and record the mass change rate of the sample during the humidity reduction process.
[0052] Table 2 Mass change rate
[0053] Humidity (%RH) Quality change rate (%) 20 0 30 3.0 40 6.0 50 9.0 60 12.0 70 15.0 80 18.0 90 21.0
[0054] It can be seen from the data that the length change rate of the sample increases under the same humidity change, indicating that the humidity sensitivity is enhanced.
[0055] Carbon nanotubes have extremely high strength and good electrical and thermal conductivity. They are evenly dispersed in the rubber solution under the action of ultrasound and mechanical stirring, which can play a toughening role. Carbon nanotubes are evenly distributed in the rubber matrix, like a "nano skeleton", preventing the expansion of cracks inside the rubber and improving the mechanical properties of the rubber layer. At the same time, they may also improve the thermal conductivity of the rubber layer, help dissipate heat, and avoid rubber aging due to local overheating.
[0056] Step 3: Pretreatment of steel plate layer: Clean the surface of the steel plate, apply a layer of special primer on the cleaned steel plate surface and dry it to obtain the steel plate layer. The primer is an epoxy primer with a drying time of 1-2 hours. The steel plate layer treated with hot dip galvanizing has no red rust for 1000 hours in the salt spray test, and the corrosion rate in a 15% sodium hydroxide solution is only 0.05g / (m 2 h), effectively improving the corrosion resistance of the steel plate layer.
[0057] Step 4: Assemble the ceramic layer, rubber layer and steel plate layer and perform post-processing: Cut the mixed rubber into a suitable size and place it between the ceramic layer and the steel plate layer. Put the stacked components into a vulcanizer for hot pressing to make the ceramic layer, rubber layer and steel plate layer composite as one. Polish the obtained material to finally obtain a composite lining. The hot pressing temperature is 140-150℃, the pressure is 10-15MPa, and the hot pressing time is 15-25min.
[0058] Example 1
[0059] A high-performance wear-resistant composite lining plate comprises a ceramic layer, a rubber layer and a steel plate layer, wherein a rubber layer is sandwiched between the steel plate layer and the ceramic layer. The preparation method thereof comprises the following steps:
[0060] Step 1. Add high-purity alumina powder into a planetary ball mill, add 3% titanium dioxide, and ball mill with anhydrous ethanol as the medium. The material-ball ratio in the ball mill is 1:3, the ball milling time is 8 hours, the rotation speed is 300r / min, the pressure in the static press is 150MPa, and the pressure is maintained for 5 minutes. The raw materials are fully mixed to obtain a slurry, and the slurry is poured into a mold, and the mold is placed in a static press to form a ceramic body. The ceramic body is placed in a high-temperature electric furnace for heating. The heating temperature in the high-temperature electric furnace is 1650°C, the heating time is 3 hours, and the heating rate is 5°C / min. Then, the furnace is cooled to room temperature to obtain a ceramic layer.
[0061] Step 2: Dissolve the thermoplastic polyurethane shape memory rubber in DMF for oil bath reaction at a temperature of 50°C and a reaction time of 4h. Then weigh the smart hydrogel precursor according to the molar ratio of NIPAAm:AAc:MBA:APS=8:2:0.1:0.01, and add the weighed NIPAAm, AAc, and MBA to the above solution for ultrasonic dispersion and mechanical stirring. The ultrasonic power is 100W, the ultrasonic time is 1h, the stirring speed is 300r / min, and the stirring time is 2h, so that the carbon nanotubes are evenly dispersed in the solution. The mass ratio of thermoplastic polyurethane shape memory rubber to DMF is 1:10, the mass ratio of smart hydrogel precursor to thermoplastic polyurethane shape memory rubber is 1:2, and the mass ratio of carbon nanotubes to thermoplastic polyurethane shape memory rubber is 0.05:1. Then pour the mixed solution into the mold and add the weighed APS initiator for cross-linking reaction. The reaction temperature is 50°C and the reaction time is 6h. After the reaction, an intelligent response multifunctional rubber layer is obtained, and then the mold is taken out, and after cooling to room temperature, the intelligent response multifunctional rubber layer is taken out of the mold to obtain a mixed rubber.
[0062] Step 3: Clean the surface of the steel plate, apply a layer of special primer on the cleaned surface of the steel plate and dry it. The primer is an epoxy primer and the drying time is 1 hour.
[0063] Step 4: Cut the mixed rubber into suitable sizes and place it between the ceramic layer and the steel plate layer. Put the stacked components into a vulcanizer for hot pressing to composite the ceramic layer, rubber layer and steel plate layer into one. Grind the obtained material to finally obtain a composite lining. The hot pressing molding temperature is 140°C, the pressure is 10MPa, and the hot pressing time is 15min.
[0064] Example 2
[0065] A high-performance wear-resistant composite lining plate comprises a ceramic layer, a rubber layer and a steel plate layer, wherein a rubber layer is sandwiched between the steel plate layer and the ceramic layer. The preparation method thereof comprises the following steps:
[0066] Step 1: Add high-purity alumina powder to a planetary ball mill, add 4% titanium dioxide, and ball mill with anhydrous ethanol as the medium. The material-ball ratio in the ball mill is 1:4, the ball milling time is 10 hours, the rotation speed is 400r / min, the pressure in the static press is 170MPa, and the pressure is maintained for 8 minutes. The raw materials are fully mixed to obtain a slurry, and the slurry is poured into a mold, and the mold is placed in a static press to form a ceramic body. The ceramic body is placed in a high-temperature electric furnace for heating. The heating temperature in the high-temperature electric furnace is 1700°C, the heating time is 4 hours, and the heating rate is 8°C / min. Then, the furnace is cooled to room temperature to obtain a ceramic layer.
[0067] Step 2: Dissolve the thermoplastic polyurethane shape memory rubber in DMF for oil bath reaction at an oil bath temperature of 80°C and a reaction time of 5h. Then weigh the smart hydrogel precursor according to the molar ratio of NIPAAm:AAc:MBA:APS=8:2:0.1:0.01, and add the weighed NIPAAm, AAc, and MBA to the above solution for ultrasonic dispersion and mechanical stirring. The ultrasonic power is 100W, the ultrasonic time is 1h, the stirring speed is 400r / min, and the stirring time is 3h, so that the carbon nanotubes are evenly dispersed in the solution. The mass ratio of thermoplastic polyurethane shape memory rubber to DMF is 1:10, the mass ratio of smart hydrogel precursor to thermoplastic polyurethane shape memory rubber is 1:2, and the mass ratio of carbon nanotubes to thermoplastic polyurethane shape memory rubber is 0.05:1. Then pour the mixed solution into the mold and add the weighed APS initiator for cross-linking reaction. The reaction temperature is 80°C and the reaction time is 7h. After the reaction, an intelligent response multifunctional rubber layer is obtained, and then the mold is taken out, and after cooling to room temperature, the intelligent response multifunctional rubber layer is taken out of the mold.
[0068] Step 3: Clean the surface of the steel plate, apply a layer of special primer on the cleaned surface of the steel plate and dry it. The primer is an epoxy primer and the drying time is 2 hours.
[0069] Step 4: Cut the rubber layer into a suitable size and place it between the ceramic layer and the steel plate layer. Put the stacked components into a vulcanizer for hot pressing to composite the ceramic layer, rubber layer and steel plate layer into one. Grind the obtained material to finally obtain a composite lining. The hot pressing molding temperature is 150°C, the pressure is 13MPa, and the hot pressing time is 20min.
[0070] Example 3
[0071] A high-performance wear-resistant composite lining plate comprises a ceramic layer, a rubber layer and a steel plate layer, wherein a rubber layer is sandwiched between the steel plate layer and the ceramic layer. The preparation method thereof comprises the following steps:
[0072] Step 1: Add high-purity alumina powder to a planetary ball mill, add 5% titanium dioxide, and ball mill with anhydrous ethanol as the medium. The material-ball ratio in the ball mill is 1:5, the ball milling time is 12 hours, the rotation speed is 500r / min, the pressure in the static press is 200MPa, and the pressure is maintained for 10 minutes. The raw materials are fully mixed to obtain a slurry, and the slurry is poured into a mold, and the mold is placed in a static press to form a ceramic body. The ceramic body is placed in a high-temperature electric furnace for heating. The heating temperature in the high-temperature electric furnace is 1700°C, the heating time is 5 hours, and the heating rate is 10°C / min. Then, the furnace is cooled to room temperature to obtain a ceramic layer.
[0073] Step 2: Dissolve the thermoplastic polyurethane shape memory rubber in DMF for oil bath reaction at a temperature of 100°C and a reaction time of 6h. Then weigh the smart hydrogel precursor according to the molar ratio of NIPAAm:AAc:MBA:APS=8:2:0.1:0.01, and add the weighed NIPAAm, AAc, and MBA to the above solution for ultrasonic dispersion and mechanical stirring. The ultrasonic power is 100W, the ultrasonic time is 2h, the stirring speed is 500r / min, and the stirring time is 3h, so that the carbon nanotubes are evenly dispersed in the solution. The mass ratio of thermoplastic polyurethane shape memory rubber to DMF is 1:12, the mass ratio of smart hydrogel precursor to thermoplastic polyurethane shape memory rubber is 1:10, and the mass ratio of carbon nanotubes to thermoplastic polyurethane shape memory rubber is 0.05:1. Then pour the mixed solution into the mold and add the weighed APS initiator for cross-linking reaction. The reaction temperature is 100°C and the reaction time is 8h. After the reaction, an intelligent response multifunctional rubber layer is obtained, and then the mold is taken out, and after cooling to room temperature, the intelligent response multifunctional rubber layer is taken out of the mold.
[0074] Step 3: Clean the surface of the steel plate, apply a layer of special primer on the cleaned surface of the steel plate and dry it. The primer is an epoxy primer and the drying time is 2 hours.
[0075] Step 4: Cut the mixed rubber into suitable sizes and place it between the ceramic layer and the steel plate layer. Put the stacked components into a vulcanizer for hot pressing to composite the ceramic layer, rubber layer and steel plate layer into one. Grind the obtained material to finally obtain a composite lining, wherein the hot pressing temperature is 150°C, the pressure is 15MPa, and the hot pressing time is 25min.
[0076] Comparative Example 1
[0077] The only difference between Comparative Example 1 and Example 1 is that the mass ratio of the smart hydrogel precursor to the shape memory rubber in Comparative Example 1 is 1:1.
[0078] Comparative Example 2
[0079] The only difference between Comparative Example 2 and Example 1 is that the mass ratio of the smart hydrogel precursor to the shape memory rubber in Comparative Example 2 is 1:15.
[0080] Comparative Example 3
[0081] Comparative Example 3 uses an ordinary lining plate, and the lining plate is a wear-resistant ceramic lining plate.
[0082] Performance Test:
[0083] The wear-resistant composite lining plates obtained in Examples 1-3 and Comparative Examples 1-2 and the ordinary lining plate of Comparative Example 3 were subjected to performance tests, and the performance test results are shown in Table 3:
[0084] Table 3 Performance test results
[0085]
[0086] It can be seen from Table 1 that the hardness of the composite linings prepared in Examples 1-3 is higher than that of the linings in Comparative Examples 1-3, and the elongation is low and the tensile strength is strong, which means that the prepared composite linings have good wear resistance, corrosion resistance and erosion resistance.
[0087] Therefore, the present invention adopts the above-mentioned high-performance wear-resistant composite lining and its preparation method, and the prepared composite lining has excellent wear resistance, strong corrosion resistance, and good anti-scouring ability, which can reduce the number of maintenance times, thereby improving the economic benefits of the enterprise.
[0088] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A high performance wear-resistant composite lining, characterized in that: It comprises a ceramic layer, a rubber layer and a steel plate layer, wherein a rubber layer is sandwiched between the steel plate layer and the ceramic layer.
2. The method for preparing a high-performance wear-resistant composite lining plate according to claim 1, characterized in that: The following steps are involved: Step 1: preparing a ceramic layer; Step 2, preparing a rubber layer; Step 3: Pretreatment of steel plate layer; Step 4: Assemble the ceramic layer, rubber layer and steel plate layer, and perform post-processing.
3. The method for preparing a high-performance wear-resistant composite lining plate according to claim 2, characterized in that: The specific operation of step one is: adding the raw materials into a planetary ball mill and ball milling with anhydrous ethanol as the medium, the raw materials are fully mixed to obtain a slurry, the slurry is poured into a mold, the mold is placed in a static press to form a ceramic body, the ceramic body is placed in a high-temperature electric furnace for heating, and then cooled to room temperature with the furnace to obtain a ceramic layer.
4. The method for preparing a high-performance wear-resistant composite lining plate according to claim 2, characterized in that: The specific operation of step two is: dissolving the shape memory rubber in an organic solvent, adding the smart hydrogel precursor and carbon nanotubes, and evenly dispersing the carbon nanotubes in the solution through ultrasonic dispersion and mechanical stirring. Then, pouring the mixed solution into a mold and adding an initiator for a cross-linking reaction, obtaining a smart responsive multifunctional rubber layer after the reaction. After cooling to room temperature, the smart responsive multifunctional rubber layer is taken out of the mold.
5. The method for preparing a high-performance wear-resistant composite lining plate according to claim 2, characterized in that: The specific operation of step three is: cleaning the surface of the steel plate, applying a layer of special primer on the cleaned surface of the steel plate and drying it to obtain a steel plate layer.
6. The method for preparing a high-performance wear-resistant composite lining plate according to claim 2, characterized in that: The specific operation of step four is: cut the intelligent response multifunctional rubber layer into a suitable size, place it between the ceramic layer and the steel plate layer, put the stacked components into a vulcanizer for hot pressing, composite the ceramic layer, rubber layer and steel plate layer into one, grind the obtained material and finally obtain a composite lining.
7. The method for preparing a high-performance wear-resistant composite lining plate according to claim 3, characterized in that: The raw materials in step 1 are high-purity alumina powder and 3-5% titanium dioxide, the material-ball ratio in the ball mill is 1:3-5, the ball milling time is 8-12h, the rotation speed is 300-500r / min, the pressure in the static press is 150-200MPa, the pressure is maintained for 5-10min, the heating temperature in the high-temperature electric furnace is 1650-1700℃, the heating time is 3-5h, and the heating rate is 5-10℃ / min.
8. The method for preparing a high-performance wear-resistant composite lining plate according to claim 4, characterized in that: In step 2, the shape memory rubber includes one of thermoplastic polyurethane and silicone rubber-based shape memory rubber, the organic solvent includes one of DMF and THF, and the smart hydrogel precursor includes one or more of N-vinyl caprolactam, acrylic acid, N,N'-methylenebisacrylamide and ammonium persulfate; The mass ratio of shape memory rubber to organic solvent is 1:8-12, the mass ratio of smart hydrogel precursor to shape memory rubber is 1:2-10, the oil bath reaction temperature is 50-100°C, the reaction time is 4-6h, the mass ratio of carbon nanotubes to shape memory rubber is 0.01-0.1:1, the ultrasonic power is 100-500W, the ultrasonic time is 1-2h, the stirring speed is 300-500r / min, and the stirring time is 2-3h; The initiator accounts for 1-5% of the total mass of the smart hydrogel precursor, the temperature of the cross-linking reaction is 50-100° C., and the reaction time is 6-8 hours.
9. The method for preparing a high-performance wear-resistant composite lining plate according to claim 5, characterized in that: In step three, the primer is an epoxy primer, and the drying time is 1-2 hours.
10. The method for preparing a high-performance wear-resistant composite lining plate according to claim 6, characterized in that: In step 4, the hot pressing molding temperature is 140-150° C., the pressure is 10-15 MPa, and the hot pressing time is 15-25 min.
Citation Information
Patent Citations
Preparation of moisture controllable polymer composite film and its application
CN101045797A
Plastic-like high-water-content hydrogel with shape memory function as well as preparation method and application of plastic-like high-water-content hydrogel
CN118047898A
Wear-resistant ceramic-rubber liner
CN201249542Y
Ceramic glue steel plate integrative wearable ceramic liner plate
CN2850905Y